Chlorination effects of a non-fullerene acceptor based on a selenium heterocyclic core for high-efficiency organic solar cells. Issue 8 (13th February 2023) - Feng, Hao; Meng, Xianglin; Fu, Liying; Liu, Chunbo; Yin, Xinxing; Zhu, Enwei; Li, Zaifang; Che, Guangbo
Abstract : The photovoltaic performance of three chlorinated NFAs based on a selenium heterocyclic core (namely BTSeIC-2Cl-γ, BTSeIC-2Cl-mix and BTSeIC-4Cl ) were researched by precisely regulating the number and position of end-group chlorine atoms. Abstract : A selenium substitution strategy combined with terminal modulation for developing high-efficiency non-fullerene acceptors (NFAs) has drawn much attention in the field of organic solar cells (OSCs). Herein, three novel NFAs featuring a benzoselenadiazole central core and IC terminal groups, namely BTSeIC-2Cl-γ, BTSeIC-2Cl-mix and BTSeIC-4Cl, were successfully designed and synthesized by modulating the numbers and positions of the chlorine atoms. Compared to the two counterpart NFAs bearing a single chlorinated γ-position and mixed positions (β or γ-position) on the IC group, di-chlorinated NFA BTSeIC-4Cl shows the strongest absorption, the shallowest lowest unoccupied molecular orbital energy level and the best molecular packing among the three acceptors. Consequently, the PM6: BTSeIC-4Cl based device exhibits a champion PCE of 16.14% with a short-circuit current density ( J SC ) of 26.92 mA cm −2, which is mainly attributed to it having the most balanced and highest electron/hole mobility and optimal blend morphology. It is worth mentioning that the obtained J SC of the PM6: BTSeIC-4Cl device is among the highest values reported for selenium-heterocyclic fused-ring acceptors with chlorinated terminal groups in the OSCs. Furthermore, the acceptor BTSeIC-2Cl-γ with a defined molecular structure achieved a better PCE of 14.91% due to its higher charge mobility and stronger π–π interaction, whereas the acceptor BTSeIC-2Cl-mix exhibited a PCE of 14.21%. This work shows that combining the selenium-heterocyclic core with the halogen-substituted regulation of terminal groups is an effective way to produce high-performance NFAs.